Efficient Design of the Microstrip Reflectarray Antenna by Optimizing the Reflection Phase Curve - Xing Chen; Qiang Chen; Pan Feng; Kama Huang (International Journal of Antennas and Propagation)
The microstrip reflectarray antenna is an attractive directional antenna combining advantages of both the reflector and the microstrip array antenna. For the design of this kind of antenna, the conventional method, which is based on the reflection phase curve, may not be effective because of the approximations made in the design procedure. The common optimization method that employs an optimization algorithm in conjunction with the full-wave simulation to optimize the antennas’ structural parameters is able to achieve better performances in comparison with the conventional method; but it is impractical for large-scale microstrip reflectarray antennas due to too many structural parameters from variable reflection elements. To tackle the design problem of the microstrip reflectarray antenna, a new method is proposed for the first time. It optimizes the reflection phase curve rather than the structural parameters and then utilizes the optimized reflection phase curve to design the antenna. A microstrip reflectarray antenna working at 5.8 GHz and with a fixed size of 300 mm × 300 mm is designed for high gain as a sample design. The results show that the proposed method has greatly improved the antenna’s gain over 2.2 dB (from 19.7 dBi to 21.9 dBi) in comparison with the conventional design method, and it only needs to optimize 6 structural parameters, in contrast to 22 for the common optimization method.